2007
DOI: 10.1097/smj.0b013e318073c7ee
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Warfarin and Levofloxacin: Case Series

Abstract: Warfarin is the most widely used oral anticoagulant and is indicated for many clinical conditions. Levofloxacin, a fluoroquinolone, is one of the most commonly prescribed antibiotics in clinical practice and is effective against Gram-positive, Gram-negative, and atypical bacteria. While small prospective studies have not revealed any significant drug-drug interaction between warfarin and levofloxacin, several case reports have indicated that levofloxacin may significantly potentiate the anticoagulation effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For warfarin, there have been discrepant findings regarding an interaction with quinolones [47]. Numerous case reports and case series [48][49][50][51][52] as well as population-based studies [35,46] have indicated that quinolones may potentiate the anticoagulant effect of warfarin and increased the risk of bleeding. In contrast, a large Canadian nested case-control study conducted in a cohort of chronic warfarin users did not find an elevated risk of hospitalisation for haemorrhage within 14 days after initiation of levofloxacin [53].…”
Section: Discussionmentioning
confidence: 99%
“…For warfarin, there have been discrepant findings regarding an interaction with quinolones [47]. Numerous case reports and case series [48][49][50][51][52] as well as population-based studies [35,46] have indicated that quinolones may potentiate the anticoagulant effect of warfarin and increased the risk of bleeding. In contrast, a large Canadian nested case-control study conducted in a cohort of chronic warfarin users did not find an elevated risk of hospitalisation for haemorrhage within 14 days after initiation of levofloxacin [53].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the clinical relevance of a potential interaction between warfarin and levofloxacin was reflected in a recent study by Vadlamudi et al [16], reporting three cases of severe bleeding complications (two hemopericardium and one retroperitoneal hematoma) occurring with concomitant administration of levofloxacin and warfarin, with one patient death resulting.…”
Section: Discussionmentioning
confidence: 94%
“…Fluoroquinolones have also been documented to interact with warfarin by inhibiting CYP1A2 [39][40][41][42][43][44][45][46]. Logistic regression of a case-crossover study done using US Medicaid data was performed to further investigate several documented warfarin interactions by measuring the increased risk of hospitalizations for gastrointestinal (GI) bleeding.…”
Section: Anti-infective Agentsmentioning
confidence: 99%